The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/jbmr.2263
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Differential Maternal and Paternal Genome Effects on Fetal Bone Phenotype at Mid-Gestation

Abstract: Parent-of-origin-dependent (epi)genetic factors are important determinants of prenatal development that program adult phenotype. However, data on magnitude and specificity of maternal and paternal genome effects on fetal bone are lacking. We used an outbred bovine model to dissect and quantify effects of parental genomes, fetal sex, and nongenetic maternal effects on the fetal skeleton and analyzed phenotypic and molecular relationships between fetal muscle and bone. Analysis of 51 bone morphometric and weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 78 publications
(146 reference statements)
1
12
0
Order By: Relevance
“…Phenotypic data and Z-score of defined gene sets (described below) were analysed using general linear models with stepwise backwards elimination5758. Variables fitted in the initiated model included main effects, i.e., feed quality (good/poor), feed level (high/low) and all two way interactions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenotypic data and Z-score of defined gene sets (described below) were analysed using general linear models with stepwise backwards elimination5758. Variables fitted in the initiated model included main effects, i.e., feed quality (good/poor), feed level (high/low) and all two way interactions.…”
Section: Methodsmentioning
confidence: 99%
“…5, Supplementary Table S3). Contributions of feed quality and level to variations in phenotypic and gene set expression using type 1 sum of square values followed previous procedures5759. The Z-score of a gene set was estimated as the mean of Z-scores of FPKM of each gene member.…”
Section: Methodsmentioning
confidence: 99%
“…More recent analyses in mouse have shown that H19 harbors miRNAs, one of which regulates cell proliferation and placental size, most likely by targeting IGF1R transcript [ 57 ]. Furthermore, correlations between H19 transcript abundance and bovine fetal skeletal muscle and bone mass suggest that development of other organs may be regulated by H19 [ 58 , 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…All tissue samples were collected on ice. Samples for DNA extraction were snap frozen in liquid nitrogen and those for RNA extraction placed in RNAlater (Ambion, Austin, United States) and stored at −80 • C after 24 h at 4 • C. For assessment of muscle mass, the spinal column with cervical, thoracic, and lumbar vertebrae and the left and right sixth rib were removed from the fetal carcass, cleaned of tissue (Xiang et al, 2014), and their lengths measured using photographic images and the image analysis program analySIS (analySIS, IBM, St Leonards NSW, Australia).…”
Section: Samples and Phenotype Datamentioning
confidence: 99%